PENERAPAN SISTEM KENDALI PID UNTUK KESTABILAN TILT-TWINCOPTER DENGAN METODE DCM - , SANI PRAMUDITA, Andi Dharmawan S.Si., M.Cs ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Twin-tiltrotor is a type of multirotor which has two propellers as propulsion located on the right and left of the body and can be moved longitudinally. Twin-tiltrotor has a Vertical Take Off and Landing system, so it can hover anytime and it can fly using fixed wing model. This study aims to design a system that can stabilize while hovering using DCM and PID control methods. DCM is a method that transform data obtained from IMU sensor (accelerometer, gyroscope, and magnetometer) and used as a refrence angle of stability of a tiltrotor controlled by PID algorithm. The results of PID will control the servo and brushless motor. The results of this study shows that the stability of the tiltrotor influenced by the position of the load and center of gravity. Beside that, by using the DCM, the result of conversion of sensor data into an angel, has an accuration Â±0.11 for roll angle and Â±0.15 for pitch angle. PID value of pitch is Kp 0.8, Ki 0.4, and Kd 0.03, while roll angle is Kp 0.32, Ki 0.03, and Kd 0.003.